Dietary patterns and the risk of tuberculosis-drug-induced liver injury: a cohort study - Wang, Jinyu; Zhou, Yarui; Zhao, Cong; Xiong, Ke; Liu, Yufeng; Zhao, Shanliang; Ma, Aiguo (Frontiers in Nutrition, 2024)
Background and Purpose: Nutrition is associated with tuberculosis-drug-induced liver injury. How dietary pattern relates to tuberculosis-drug-induced liver injury is still unknown. The objective is to explore the relation between dietary patterns and the risk of tuberculosis-drug-induced liver injury. Methods: This cohort study was conducted at two hospitals in Shandong Province, China between 2011 and 2013. A total of 605 tuberculosis patients were included in the final analysis. The blood aspartate aminotransferase or alanine aminotransferase level was monitored through the six-month tuberculosis treatment. The semi-quantitative food frequency questionnaires were used to survey the dietary intake in the second month of the tuberculosis treatment. China healthy diet index (CHDI), which was previously validated in Chinese population, was used as a priori dietary pattern. Posteriori dietary patterns were extracted by principal component analyses (PCA). Results: The CHDI was negatively associated with the risk of liver injury [adjusted odds ratio (aOR) per standard deviation (SD) (95% CI): 0.61 (0.40-0.94)] and liver dysfunction [aOR per SD (95% CI): 0.47 (0.35-0.64)] in the multivariate logistic model. A positive association between “Organ meat, poultry, and vegetable oil” dietary pattern scores (extracted by PCA) and the risk of liver injury [aOR (95% CI): 3.02 (1.42-6.41)] and liver dysfunction [aOR (95% CI): 1.83 (1.09-3.05)] was observed. Conclusion: In conclusion, a high CHDI score was a protective factor for tuberculosis-drug induced liver injury, while the “Organ meat, poultry, and vegetable oil” dietary pattern, which was rich in organ meat, poultry, vegetable oil, and low in vegetables, was an independent risk factor for tuberculosis-drug induced liver injury.